فاعلية برنامج إرشادي تكاملي قائم على العلاج بالمعني وبعض قوى الشخصية في تحسين جودة الحياة لدى عينة من المراهقين - عمر، عبدالمنعم علي علي (جامعة عين شمس - كلية التربية, 2019)
هدف البحث إلى تحسين جودة الحياة لدى عينة من المراهقين من خلال إعداد برنامج إرشادي تكاملي قائم على العلاج بالمعني وبعض قوي الشخصية. ثم التحقق من مدى فعالية البرنامج في تحسين جودة الحياة لدى عينة الدراسة. ثم التعرف على مدى استمرارية أثر البرنامج الإرشادي بعد فترة المتابعة. وشارك في الدراسة (٢٦) طالبا من طلاب الفرقة الثانية والثالثة بالمرحلة الثانوية، تراوحت أعمارهم ما بين ١٦: ١٨ سنة، تم تقسيمهم إلى مجموعتين، إحداهما تجريبية والأخرى ضابطة، بواقع (١٣) طالبا في كل مجموعة. واستخدمت الدراسة مقياس المستوى الاجتماعي الاقتصادي للأسرة إعداد عبد العزيز الشخص (٢٠٠٦)، ومقياس جودة الحياة إعداد الباحث، واستمارة المقابلة الشخصية إعداد الباحث، والبرنامج الإرشادي المقترح إعداد الباحث. وأشارت نتائج الدراسة إلى وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات أفراد المجموعة التجريبية على مقياس جودة الحياة في كل من القياسين القبلي والبعدي. ووجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطي رتب درجات أفراد المجموعتين التجريبية والضابطة على مقياس جودة الحياة في القياس البعدي. كما أشارت النتائج إلى عدم وجود فروق ذات دلالة إحصائية بين متوسطي رتب درجات أفراد المجموعة التجريبية على مقياس جودة الحياة في كل من القياسين البعدي والتتبعي.
This study aimed at improving the quality of life among a sample of adolescents through preparing an integrative counseling program based upon the meaning therapy and some Personality strengths, investigating the effect of this program in improving the quality of life among the study sample, and investigating the continuity of the program's effect after the follow-up period. The participants were (26) students enrolled in the second and third grades in the secondary school stage, their ages were ranged between (16) and (18) years, and were divided into two groups: experimental (13 students) and control (13 students). The study utilized Family Socio-Economic Status Scale (prepared by Abdel- Aziz El-Shakhs, 2006), the Quality of Life Scale (Prepared by the researcher), the Interview Form Checklist and the Proposed Counseling Program (Prepared by the researcher). The study results revealed that there were statistically significant differences at level (0.01) between the ranks mean scores of the students of the experimental group in the pre and posttests of the Quality of Life Scale. In addition, there were statistically significant differences at level (0.01) between the ranks means scores of the students of the experimental group and those of the control group in the post-test of the Quality of Life Scale. Moreover, the results revealed that there were no statistically significant differences between the ranks mean scores of the students of the experimental group in the post and follow-up tests of the Quality of Life Scale.
Keywords: البرنامج الإرشادي -- العلاج بالمعني -- قوى الشخصية -- جودة الحياة -- المراهقة